Research on energy efficiency optimization assisted by active reconfigurable intelligent surface in high-speed railway scenarios - DING Qingfeng; ZOU Zhixiang (Dianxin kexue)
In addressing the challenge of the multiplicative fading introduced by passive reconfigurable intelligent surface (RIS) in high-speed railway scenarios, an effective solution is the deployment of an active RIS. However, the conventional fully-connected architecture of active RIS, characterized by a multitude of active elements, results in excessive hardware costs and power consumption. Consequently, a sub-connected architecture of active RIS was proposed, with the aim of simultaneously considering the system's energy efficiency and the transmission rate in train-ground communication. Initially, a system model for active RIS-assisted multi-user scenarios was established, taking into account the distinctive features of the high-speed railway environment. Subsequently, the problem of maximizing system energy efficiency was formulated by considering constraints on the maximum transmission power of the base station, the transmission power of the active RIS, and the phase-shift matrix of the active RIS. Through the utilization of Lagrange dual transformation and quadratic transformation from fractional programming theory, the non-convex problem was transformed into a convex optimization problem. Finally, an alternating optimization algorithm was proposed for the joint optimization of beamforming and the phase-shift matrix of the active RIS. Simulation results indicate that, compared to traditional passive RIS and fully-connected of active RIS architectures, the proposed solution effectively addresses the multiplicative fading issue. Additionally, the proposed solution achieves higher energy efficiency while meeting user transmission rate requirements.